2005
DOI: 10.1074/jbc.m410413200
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum Stress Stimulates Heme Oxygenase-1 Gene Expression in Vascular Smooth Muscle

Abstract: Heme oxygenase-1 (HO-1) is a cytoprotective protein that catalyzes the degradation of heme to biliverdin, iron, and carbon monoxide (CO). In the present study, we found that endoplasmic reticulum (ER) stress induced by a variety of experimental agents stimulated a time-and concentration-dependent increase in HO-1 mRNA and protein in vascular smooth muscle cells (SMC). The induction of HO-1 by ER stress was blocked by actinomycin D or cycloheximide and was independent of any changes in HO-1 mRNA stability. Luci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
70
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(77 citation statements)
references
References 58 publications
7
70
0
Order By: Relevance
“…Previous studies identified oxidized low-density lipoprotein, peroxynitrite, homocysteine, and inflammatory cytokines as potent inducers of HO-1 (3,8,11,12,30). Furthermore, growth factors such as plateletderived growth factor, transforming growth factor-␤, and angiotensin II, which are present in vascular lesions, are also able to upregulate HO-1 expression (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies identified oxidized low-density lipoprotein, peroxynitrite, homocysteine, and inflammatory cytokines as potent inducers of HO-1 (3,8,11,12,30). Furthermore, growth factors such as plateletderived growth factor, transforming growth factor-␤, and angiotensin II, which are present in vascular lesions, are also able to upregulate HO-1 expression (17).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, growth factors such as plateletderived growth factor, transforming growth factor-␤, and angiotensin II, which are present in vascular lesions, are also able to upregulate HO-1 expression (17). Interestingly, the induction of HO-1 by HOCl and several atherogenic factors is mediated through the activation of Nrf2 (3,12,30). However, the upstream signaling pathways that lead to the activation of Nrf2 may differ between stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…c-Jun can form part of the AP-1, StRE [31], and EpRE binding complexes [64] and further, StRE-and EpRE-mediated induction of HO-1 has been shown previously in rat cell lines [31,64,65]. Although no change in total EpRE binding was observed in response to HNE, the EpRE and/ or StRE enhancer elements could still be involved in the increase in HO-1 mRNA via transcription factor complex remodeling [39], specifically through activated c-Jun joining the complex and potentially displacing an inhibitor [66].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, it has been reported that in cultured vascular smooth muscle cells, endoplasmic reticulum stress increased HO-1 mRNA and protein via the ARE, and this was associated with cell survival. 49 The "endoplasmic reticulum stress response" constitutes a general response to endoplasmic reticulum-associated stress such as unfolded proteins, glucose starvation, and disruption of intracellular calcium homeostasis. Endoplasmic reticulum-initiated cell death pathways are increasingly recognized as playing important roles in several diseases, including ischemia/reperfusion injury, heart disease, and diabetes.…”
Section: Response To Physical Stressmentioning
confidence: 99%